Analysis of the Meaning of the Hadith on Wiping the Khuf in the Book of Al-Żikrā by AGH. KH. Lanre Said: A Textual Interpretation of Hadith - Munadi, Radhie; Rayyn, I Gusti Bagus Agung Perdana (Proceedings of International Conference on Muslim Society and Thought, 2024)
Wiping the khuf is one of the actions taught by the Prophet Muhammad (PBUH) as a form of relief when purifying. Meanwhile, the book of Al-Żikrā is one of the works of an Indonesian scholar from South Sulawesi, namely AGH. KH. Lanre Said. But it is still very rare to be discussed and studied further. The main objective of this study is to analyse and elaborate on the meaning of the Prophet Muhammad’s hadith about wiping the khuf in the book of Al-Żikrā. In this research, the ma’ān al-ḥadīṡ approach is used by performing the technique of textual interpretation of hadith initiated by hadith scholars, namely Arifuddin Ahmad, as a step in analysing the hadith, which is the object of the research. This research is descriptive qualitative literature research. The results show that, when viewed from the diversity of narration techniques, the hadith is narrated in meaning and narrated in complete and incomplete. As for the variety of language forms and styles, it was found that the hadith was delivered in three dialects of the language, namely Fushah, Persian, and Sham, in the form of affirmative dialogue, and was classified as a sentence full of meaning and logic. In terms of the diversity of the content of the hadith, it is found that the content of the hadith is related to the issue of worship, in this case, mahdah worship and legal provisions. On the other hand, AGH. KH. Lanre Said tends to interpret the hadith textually, saying that what is meant by khuf is shoes in general, and the hadith contains legal provisions relating to the permissibility of wiping the shoes instead of wiping the feet during ablution